Features of coatings deposition in combined stationary-pulsed operation mode of the magnetron sputtering system - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Bizukov, А.А.; Girka, A.I. (Вопросы атомной науки и техники, 2017)
The results of researches of the combined stationary-pulsed operating mode of longitudinal planar magnetron sputtering system (MSS) with a magnetically isolated anode and with the additional pulsed high-current, high-voltage power supply are presented. It is shown that the increasing of duration of the pulse discharge with decaying current and voltage is not advisable for effective intensification of MSS target sputtering process and increase of mass transfer of substance on substrate. The existence of the optimal ratio between parameters of the stationary and pulsed magnetron discharge is shown.